PEMBIAYAAN DARI IKLAN LEMBAGA PENYIARAN PUBLIK DAERAH RADIO SWARA TANGERANG GEMILANG (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2019)
The research aims to produce studies in the form of academic texts that can be used as guidelines and financing solutions for public broadcasting institutions of the Swara Regional Government Radio specifically and Regional Government Radios in Indonesia in general. This study also aims to identify regional revenues and expenditures that have been obtained so far and are expected to be able to obtain solutions to explore regional revenues and expenditures in the future, especially revenues derived from advertising. The study was conducted using qualitative methods which were preceded by documentation studies to map issues related to the research topic. After mapping the problem, the research continued with observations to public broadcasters, in-depth interviews (in-depth interviews and focus group discussions (FGD). As a final step, data analysis was carried out by data triangulation, triangulation methods and theory triangulation. The final step to be taken is the researcher triangulation.The findings obtained by the researcher will be generated in analyzing the data obtained so that not only can the results of a comprehensive analysis be obtained, but also the results of universal analysis can also be obtained. Keywords: Advertising, financing, radio, public broadcasting